The Influence of Working Capital Management on Business Performance: Moderating Effect of COVID-19 - Badruzaman, Jajang (SMART Insight, 2023)
The aim of this research is to find the influence between Working CapitalManagement and Business Performance in COVID-19 era. The quantitativeresearch methods, multiple regressions, secondary data and purposive samplinghave been worked out. The authors have collected a panel of 16 of HealthcareSector Company from Indonesia Stock Exchange in 2018-2021. The results ofthis study indicate that Working Capital Management measured by GWCR hasan effect on business performance and NWCR has no effect on businessperformance measured by ROA and ROE. Meanwhile, Covid-19 did notmoderate the influence between GWCR on business performance and Covid-19was able to moderate the relationship between NWCR and businessperformance. By validating the findings with previous researchers, this researchwill contribute to the literature and business surveys. It will benefit academic,social and practical behavior.